Evidence for low-density lipoprotein receptor-mediated uptake of benzoporphyrin derivative. - Allison, B. A. (Nature Publishing Group, 1994)
Plasma lipoproteins, such as low-density lipoprotein (LDL), have been proposed to enhance the delivery of hydrophobic photosensitisers to malignant tissue since tumour cells have been shown to have increased numbers of LDL receptors. We have investigated the role of this receptor in the cellular accumulation of the photosensitiser benzoporphyrin derivative (BPD). We observed that: (1) [14C]BPD-LDL accumulation by LDL receptor-negative fibroblast cell lines was insignificant compared with normal cell lines; (2) there was no evidence that BPD dissociated from LDL during incubation with the cells; and (3) chemical acetylation of LDL markedly decreased the uptake of [14C]BPD-LDL. We conclude, therefore, that virtually all of the photosensitiser accumulated by the cells was due to specific binding and internalisation via the LDL receptor. Subsequent in vivo studies in M-1 (methylcholanthrene-induced rhabdomyosarcoma) tumour-bearing DBA/2J mice showed that tumour accumulation of BPD associated with native LDL was significantly (P < 0.01) enhanced over that of acetyl-LDL-associated BPD. These results indicate that the LDL receptor is responsible for the accumulation of LDL-associated BPD both in vitro and in vivo. Thus, utilisation of this delivery system may provide for improvements in photodynamic therapy in clinical practice.